GALANT REFLEX IN THE DIAGNOSIS OF SPINAL DISORDERS IN NEWBORNS - Загородникова, Ольга Александровна; Коновалова, Нина Геннадьевна; Васильченко, Елена Михайловна; Ренге, Людмила Владимировна (Medicine in Kuzbass, 2019)
The aim – to study Galant reflex induced by paravertebral point-pressure, and evaluate its ability for the topical diagnosis of spinal cord injuries in newborns. Material and methods. A total of 548 children were examined at maternity hospitals and the City Children’s Hospital N 4 in Novokuznetsk. Mother’s obstetric history, birth process, Apgar assessment, early adjustment period, and neurological status were taken into account. Galant reflex was induced by two ways: by bar irritation and by point-pressure. Results. We surveyed 305 babies without neurological deviation. In this group Galant reflex was invoked in full by bar irritation as well as by point-pressure. Full reflex response was obtained by single point-pressure at the level of C7. In 243 cases maternal obstetrical history and birth process were burdened. Early adaptation period flowed abnormally, and newborns had some neurological deviations. Signs of cervical birth trauma were identified in 224 newborns. Galant reflex was induced by point-pressure from Th5 level and below. Only spinal cord segments innervating extensors of lumbar and pelvic departments responded. 19 newborns had signs of lumbar spinal cord injury. Their reflex response aroused from the level C7 to Th7, only the upper sections of the body formed the reflex arc. Conclusion. The evaluation of Galant reflex by point stimulation of paravertebral areas allows to determine clinically the state of spinal cord segmental apparatus in newborns.